Communications. Issue 35 (28th June 2016) - Kang, Dong‐Ho; Pae, Seong Ryul; Shim, Jaewoo; Yoo, Gwangwe; Jeon, Jaeho; Leem, Jung Woo; Yu, Jae Su; Lee, Sungjoo; Shin, Byungha; Park, Jin‐Hong
Abstract : An ultrahigh performance MoS2 photodetector with high photoresponsivity (1.94 × 10 6 A W –1 ) and detectivity (1.29 × 10 12 Jones) under 520 nm and 4.63 pW laser exposure is demonstrated. This photodetector is based on a methyl‐ammonium lead halide perovskite/MoS2 hybrid structure with (3‐aminopropyl)triethoxysilane doping. The performance degradation caused by moisture is also minimized down to 20% by adopting a new encapsulation bilayer of octadecyltrichlorosilane/polymethyl methacrylate.